2016
DOI: 10.18294/sc.2016.932
|View full text |Cite
|
Sign up to set email alerts
|

¿Sabemos lo que comemos?: Percepciones sobre el riesgo alimentario en Cataluña, España

Abstract: This article describes and analyzes social perceptions regarding food risks in Catalonia (Spain). In particular it uses the narratives of informants to determine which foods are perceived as dangerous and how, when, where and why this perception of risk develops. Through a qualitative research study, we explored how lay discourses are constructed and managed, creating diverse imaginaries regarding food risk that do not always coincide with the biomedical view. It is highlighted that food risk is not always ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 11 publications
0
7
0
7
Order By: Relevance
“…Most of the figures in the food diaries are of a transparent body showing the organs (stomach, lungs, liver, kidneys, intestines), and primarily, the digestive system. A previous study had already shown that food occupied a fundamental place in perceptions of the risk of contamination by synthetic chemical substances [28][29][30].…”
Section: Representation Of the Body: Separate Organs And Fluids In Momentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the figures in the food diaries are of a transparent body showing the organs (stomach, lungs, liver, kidneys, intestines), and primarily, the digestive system. A previous study had already shown that food occupied a fundamental place in perceptions of the risk of contamination by synthetic chemical substances [28][29][30].…”
Section: Representation Of the Body: Separate Organs And Fluids In Momentioning
confidence: 99%
“…For her, the liver is the organ that metabolizes the chemicals, while the kidneys are the organs that eliminate them in part, with the remnants being transmitted to the fetus through the placenta. Although the elimination of chemical substances is considered a part of the excretory processes of defecating, urinating and sweating, the women think that there is also a proactive way to eliminate these substances through certain practices to detoxify the body, such as eating organic or other specific foods [30], and through activities such as sports, hydration or massages. Some women confuse the elimination of chemical compounds with the elimination of toxins and attribute these practices to different processes.…”
Section: Elimination and Transmission: Some Substances Are Excreted Amentioning
confidence: 99%
“…However, in general terms, naturalness versus artificiality of a food is linked primarily to "what is good to eat" and the fact of not having been transformed or manipulated industrially in any of its different phases or culinary production, distribution, conservation and/or preparation. In turn, these categories are compared with others such as the rural (the natural) opposite the urban (the artificial), the traditional (natural) opposite the modern (artificial), the nearby (natural) opposite the distant (artificial), or the local (natural) opposite the global (artificial) (Zafra Aparici et al, 2016):…”
Section: Conflictos Intrapersonales Entre Lo Que Me Gustaría Comer Ymentioning
confidence: 99%
“…I worry because you must choose everything possible of Spanish origin, because the snacks are un alimento, se vincula mayoritariamente a "lo bueno para comer" y al hecho de no haber sido transformado o manipulado industrialmente en alguna de sus diferentes fases de producción, distribución, conservación o preparación culinaria. A su vez, estas categorías se equiparán con otras como son lo rural (lo natural) frente lo urbano (lo artificial), lo tradicional (natural) frente lo moderno (artificial), lo cercano (natural) frente lo lejano (artificial) o lo local (natural) frente lo global (artificial) (Zafra Aparici et al, 2016):…”
Section: Conflictos Intrapersonales Entre Lo Que Me Gustaría Comer Yunclassified
“…Dentro de este eje tenemos la fortuna de contar con tres artículos: 1) "¿Sabemos lo que comemos? : Percepciones sobre el riesgo alimentario en Cataluña" (6) , de Eva Zafra Aparici y colaboradores, de la Universitat Rovira i Virgili, España; 2) "Alimentación y riesgos para la salud: visiones sobre la alimentación saludable y prácticas alimentarias de mujeres y varones de clase media en el Área Metropolitana de Buenos Aires" (7) , de Betina freidin, del Instituto de Investigaciones Gino Germani, Argentina; y 3) "Las madres y la publicidad de alimentos dirigida a niños: percepciones y experiencias" (8) , de Luciana Castronuovo y colaboradores, de la Fundación Interamericana del Corazón, Argentina. Los tres abordan las percepciones de sectores sociales que pueden elegir qué comer.…”
Section: Representaciones Socialesunclassified